Upaya Perbaikan Kualitas Buah Anggur Bali (Vitis vinifera L. Var. Alphonso Lavallee) Melalui Aplikasi GA dari Ekstrak Rebung Bambu pada Stadia Bunga Mekar - ISNAINI ISNAINI; NI NYOMAN ARI MAYADEWI; I NENGAH ARTHA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The Attempt to Improve the Quality of Balinese Grapevine Fruits (Vitis vinifera L. Var Alphonso Lavallee) With GA Application from Bamboo Shoot Extract at The Blooming Phase Balinese table grape is one of the superior fruit in Bali. Balinese table grape less salable than imported grapes because of the lack of the sweetness, small fruit size and the presence of the seeds are the weaknesses of Balinese table grapes quality. This study aims to determine the effectiveness of the bamboo shoots extract at the blooming phase to improve fruit quality. The experimental design used was a Randomized Block Design with 5 treatments and 5 replications. The treatments are different concentration of bamboo shoot extract including without bamboo shoot extract (control), 25%, 50%, 75% and 100% of bamboo shoot extract. The observed variables were fruitset length, number of fruit per fruitset, fruit weight per fruitset, weight per fruit, number of seeds per fruit, total soluble solids and organoleptic test. The result showed that 100% bamboo shoot extract concentration was able to improve the quality of Balinese grapevines with fruitset length of 20.93 cm increased by 157.3% compared to control, the number of seeds 1.36 decreased by 54% compared to control, and total soluble solids 8.79oBrix increased by 122.8% compared with controls.